Ovis aries Papillomavirus 3 in Ovine Cutaneous Squamous Cell Carcinoma. (September 2017) - Vitiello, Veronica; Burrai, Giovanni P.; Agus, Mariagrazia; Anfossi, Antonio G.; Alberti, Alberto; Antuofermo, Elisabetta; Rocca, Stefano; Cubeddu, Tiziana; Pirino, Salvatore
Squamous cell carcinoma (SCC) is a common malignancy affecting humans and other animals. Papillomaviruses (PVs) are frequently reported as causal agents of cutaneous benign and malignant epithelial lesions in different animal species, but only few studies have investigated their role in ovine SCC. In this study, we explore the possible involvement of the Ovine aries PVs (OaPV1, OaPV2, OaPV3) in cutaneous SCC using an integrated histological and molecular approach. Forty cutaneous SCCs from different anatomical locations of Sardinian sheep and 40 matched non-SCC samples were evaluated histologically and by polymerase chain reaction (PCR) to assess the presence of ovine PVs. In addition, DNA in situ hybridization (ISH) and reverse transcription–polymerase chain reaction (RT-PCR) were carried out to evaluate the cellular localization and viral transcriptional activity, respectively. OaPV3 DNA was detected in 26 of 40 (65%) SCCs and in 12 of 40 (30%) non-SCC samples using PCR. OaPV1 and OaPV2 were not detected. OaPV3 viral DNA was observed by ISH in malignant epithelial squamous cells of 18 of 40 (45%) SCCs. In addition, the viral transcriptional activity was identified in 24 of 40 (60%) SCCs by RT-PCR. Notably, a higher viral positivity was observed in SCCs compared with non-SCC samples. The considerable infection rate of OaPV3 in the most common skin tumor of the sheep suggests that PV could represent a key factor in the onset of ovine SCC.